Real Time- Polymerase Chain Reaction (RT-PCR) Test to Diagnose Brucellosis in Sheep in ANBAR Province - Sabaa nazoa; Bashar Noomi; Ayad Ebraheem (Basrah Journal of Veterinary Research)
The aims of the study were to determine incidence ratio of brucellosis in aborted ewes in Anbar governorate using real time PCR technique and bacterial culture and evaluating the efficiency of bacterial culture. 50 samples of stomach contents of an aborted fetus and vaginal swabs from aborted ewes were collected. The incidence ratio of brucellosis in ewes in Anbar governorate were 72% in PCR test However in bacterial culture were 46%. The positive prediction value and Negative prediction value and Sensitivity and Specificity of bacterial culture were (100%, 51.8 %,63%,100%) respectively when use Real time PCR as an assessment test. Conclusions: Anbar province is endemic with brucellosis, especially in sheep. The Real Time PCR is a fast, easy and accurate test in detecting even small numbers of bacteria in a sample, Significant superiority of polymerase chain reaction technology over bacterial culture.